More answers

(x + 3)(x - 2)(x + 2)

Q: How do you factor x3 plus 3x2-4x-12?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

x2(x3 + 1) is the best you can do there.

x3 - 3x2 + x - 3 = (x2 +1)( x - 3)

x3 + 8 = x3 + 23 = (x + 2)[x2 - (x)(2) + 22] = (x + 2) (x2 - 2x + 4)

If you mean "factors", the two monomials have the common factor x2. Divide each factor by x2 to get the other factor.

2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7

Related questions

x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x3+27y3 = (x+3y) · (x2-3xy+9y2)

x2(x3 + 1) is the best you can do there.

x(x^2 + 2)

(x + 2)(x^2+4)

(x2 - xy + y2)(x + y)

(x + 1)(x2 - x + 1)

x3 - 2x2 + x - 2 =(x - 2)(x2 + 1)

x3 - 3x2 + x - 3 = (x - 3)(x2 + 1)

3 - 3x + x2 - x3 = (1 - x)(x2 + 3)

x3 - 3x2 + x - 3 = (x2 +1)( x - 3)